L’Université mise en scène - Winfried Müller (Revue d’Histoire des Sciences Humaines)
The first part of the essay observes the development of the modern anniversary culture whose roots were formed through the introduction of the Holy Year by Pope Bonifaz the VIII in 1300. Since 1475, this tradition has continued to be held once every 25 years. Around 1500 universities adapted this cycle to celebrate their own founding. In difference to the Holy Year of the old church especially protestant universities (Tübingen 1578, Heidelberg 1587, and Wittenberg 1602) developed the tradition of academic anniversaries, each marked by celebrations, speeches and commemorative publications. The specific elements of this university anniversary culture are discussed in the second part of the article. Finally, the example of the 650th anniversary of the University of Vienna (2015) will show current tendencies of university anniversaries such as the accentuation of contemporary history and women’s history.